Roadmap on wavefront shaping and deep imaging in complex media. (1st October 2022) - Gigan, Sylvain; Katz, Ori; de Aguiar, Hilton B; Andresen, Esben Ravn; Aubry, Alexandre; Bertolotti, Jacopo; Bossy, Emmanuel; Bouchet, Dorian; Brake, Joshua; Brasselet, Sophie; Bromberg, Yaron; Cao, Hui; et al.
Abstract: The last decade has seen the development of a wide set of tools, such as wavefront shaping, computational or fundamental methods, that allow us to understand and control light propagation in a complex medium, such as biological tissues or multimode fibers. A vibrant and diverse community is now working in this field, which has revolutionized the prospect of diffraction-limited imaging at depth in tissues. This roadmap highlights several key aspects of this fast developing field, and some of the challenges and opportunities ahead.